miR-342-5p downstream to Notch enhances arterialization of endothelial cells in response to shear stress by repressing MYC - Xiaoyan Zhang; Jiaxing Sun; Peiran Zhang; Ting Wen; Ruonan Wang; Liang Liang; Ziyan Yang; Jiayan Li; Jiayulin Zhang; Bo Che; Xingxing Feng; Xiaowei Liu; et al. (Elsevier, 2023)
During vascular development, endothelial cells (ECs) undergo arterialization in response to genetic programs and shear stress-triggered mechanotransduction, forming a stable vasculature. Although the Notch receptor is known to sense shear stress and promote EC arterialization, its downstream mechanisms remain unclear. In this study, the Notch downstream miR-342-5p was found to respond to shear stress and promote EC arterialization. Shear stress upregulated miR-342-5p in a Notch-dependent manner in human umbilical vein endothelial cells (HUVECs). miR-342-5p overexpression upregulated the shear stress-associated transcriptomic signature. Moreover, miR-342-5p upregulated arterial markers and promoted EC arterialization in a Matrigel plug assay and retinal angiogenesis model. In contrast, miR-342-5p knockdown downregulated arterial markers, compromised retinal arterialization, and partially abrogated shear stress and Notch activation-induced arterial marker upregulation. Mechanistically, miR-342-5p overexpression suppressed MYC to repress EC proliferation and promote arterialization, achieved by promoting MYC protein degradation by targeting the EYA3. Consistently, EYA3 overexpression rescued miR-342-5p-mediated MYC downregulation and EC arterialization. In vivo, miR-342-5p expression was notably decreased in the ligated artery in a hindlimb ischemia model, and an intramuscular injection of miR-342-5p promoted EC arterialization and improved perfusion. In summary, miR-342-5p, a mechano-miR, mediates the effects of shear stress-activated Notch on EC arterialization and is a potential therapeutic target for ischemic diseases.